Mediation analysis of the impact of the Zimbabwe Harmonized Social Cash Transfer Programme on food security and nutrition. (January 2022) - Pace, Noemi; Sebastian, Ashwini; Daidone, Silvio; Prifti, Ervin; Davis, Benjamin
Highlights: The paper studies the effects of the Harmonized Social Cash Transfer programme on food security and nutrition. The total effect ranges between a 11 and 16 percent increase with respect to the baseline mean for the dietary diversity score and the number of food items consumed, respectively. The mediation analysis disentangles the total effect into direct and indirect effect (mediated by agricultural activities) Between 10 and 21 percent of the total effect is mediated by agricultural activities. The programme contributes to household welfare by guaranteeing beneficiaries a higher purchasing power and by boosting their agricultural activities. Abstract: This paper analyses the causal effects of the Zimbabwe Harmonized Social Cash Transfer (HSCT) programme on food security and nutrition after 12 months of implementation. Through mediation analysis, we disentangle the total effect of the programme on its direct effect due to the greater liquidity of beneficiary households, which increases the affordability of food, and its indirect effect mediated by an increase in agricultural activities. We find a total effect of cash transfers on food security and nutrition ranging between a 11 and 16 percent increase with respect to the baseline comparison mean for the household dietary diversity score and number of food items consumed, respectively. Causal mediation analysis shows that most of the effects are driven by the increased liquidity of HSCT beneficiaries. However, approximately between 10 and 21 percent of the total effect is mediated by agricultural activities, suggesting that cash transfer programmes not only play a protective role against food insecurity but also a promoting role towards more diversified nutrition.